A systematic literature review of implementation six sigma in manufacturing industries - Indra Setiawan; Fransisca Debora (Universitas Mercu Buana, 2020)
The Six Sigma approach has received a lot of attention in various industrial sectors from the manufacturing industry to the service industry. More specific knowledge about Six Sigma has grown rapidly. Much of the training and research on Six Sigma is carried out in various industries and university. This literature review related to Six Sigma purpose to provide an overview of Six Sigma implementation in the manufacturing industries. The Six Sigma approach that has been introduced and implemented for a long time is DMAIC (Define, Measure, Analyze, Improve, and Control). This paper discusses the published literature related to Six Sigma ranging from 2015 to 2020. This paper involves the study review of 50 papers related to the implementation of Six Sigma of known database search including Elsevier, Science Direct, Emerald Insight and Google Scholars. This literature review contains results from a variety of different perspectives. The perspective includes the focus of the industry, the focus of the number of distribution by country, the focus of the year of publication and the focus of the number of publishers. In fact, this is useful for all types of manufacturing industries to find solutions to problems. The paper also provides advantages for researchers next to add to the literature.